Prospects for Resolving the “Durand Line” Problem - Rahimov, Sardor (Indonesian Journal Publisher, 2025)
This study aims to analyze the prospects for resolving the long-standing Durand Line border dispute between Afghanistan and Pakistan, which has remained one of the most critical issues affecting bilateral relations and regional stability. Using qualitative methods with comparative and content analysis, the research draws upon scholarly works, historical documents, and expert opinions regarding the historical, political, and legal aspects of the border conflict. The results indicate that despite numerous initiatives and proposals—including the creation of joint commissions, international mediation, or the adoption of soft-border models—no practical progress has been achieved in resolving the issue. Armed clashes continue to occur in border areas, while the return of the Taliban in 2021 further complicated the conflict. The study also finds that external actors and geopolitical rivalries have made the conflict more complex, hindering long-term solutions. In conclusion, the Durand Line dispute is unlikely to be resolved in the near future. However, potential solutions may lie in bilateral negotiations, international legal mechanisms, or regional platforms such as the Shanghai Cooperation Organization. A diplomatic and institutional approach, rather than confrontation, is necessary to promote stability and cooperation between Afghanistan and Pakistan.